2018
DOI: 10.1002/lary.27585
|View full text |Cite
|
Sign up to set email alerts
|

Correlating laryngoscopic appearance of laryngeal lesions with histopathology

Abstract: Objectives/Hypothesis Meticulous scrutiny of laryngeal lesions with laryngoscopes and microscopes often identify angiogenic activity, one of the hallmarks of neoplastic and preneoplastic lesions. The aim of this study was to determine if there is an association between laryngoscopic appearance and histopathology of laryngeal lesions based on operative biopsies. Study Design Retrospective case‐control study. Methods One hundred forty‐four laryngeal biopsies from 92 patients between 2015 and 2017 met inclusion c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“… 3 Keratosis is often used interchangeably with leukoplakia , even though the latter means “white patch.” Keratosis may be associated with phonotraumatic lesions, and these generally have low malignant potential. 4 - 6 All other glottic keratoses pose a difficult problem for clinical management. The histology and behavior of glottic keratosis can be frustratingly difficult to predict, as lesions can present on a spectrum anywhere from completely benign growth to invasive malignancy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“… 3 Keratosis is often used interchangeably with leukoplakia , even though the latter means “white patch.” Keratosis may be associated with phonotraumatic lesions, and these generally have low malignant potential. 4 - 6 All other glottic keratoses pose a difficult problem for clinical management. The histology and behavior of glottic keratosis can be frustratingly difficult to predict, as lesions can present on a spectrum anywhere from completely benign growth to invasive malignancy.…”
mentioning
confidence: 99%
“… 10 - 12 The present study is predicated on the observation in our prior study that certain keratotic glottic lesions were found to harbor malignancy on histopathology despite having no vascular speckling. 5 In this study, we sought to determine the relative significance of different laryngoscopic findings based on their correlation with histopathology. The significant laryngoscopic findings could alert clinicians to lesions that need expedient biopsy and treatment.…”
mentioning
confidence: 99%
“…proposed evaluation of only the roughness of leukoplakia, but not the mucosal red zone around it. In addition, previous studies have shown that under routine laryngoscopy, hyperaemia 13 and vascular stippling 4 are closely associated with dysplasia and the malignancy of vocal fold leukoplakia.…”
Section: Discussionmentioning
confidence: 98%
“…Laryngoscopy is a widely used examination method for the diagnosis of vocal fold leukoplakia. However, given the high similarity in manifestation of different pathological types of vocal fold leukoplakia, it is difficult to accurately evaluate the degree of dysplasia in vocal fold leukoplakia and to determine whether there is cancerisation by routine laryngoscopy 4 . This often results in over- or under-treatment due to misdiagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…A more recent study by Anis sought to further identify correlations between laryngoscopic appearances of lesions with histopathology. In this retrospective review of 144 laryngeal lesions from 92 patients, cases of patients with biopsy‐proven dysplasia or malignancy were compared to controls with benign pathology.…”
Section: Literature Reviewmentioning
confidence: 99%